Employee Performance Achievement Through application of principles “the right man in the right place” in organizational structure at the foundation miftahussalam islamic education Medan - Henny Purnama Dewi (Jurnal Mantik, 2021)
Employees have a major role in every organizational activity, because employees become planners, actors, and determinants of the realization of organizational system goals. Organizational goals will be easier to achieve if employees are placed in positions that match their competencies. Therefore, it is very necessary to have a good organizational structure where in the organizational structure one of the management principles is applied, namely "The Right Man In The Right Place". This study aims to determine the effect of organizational structure on the performance of employees of the Miftahussalam Islamic Education Foundation Medan. Sampling technique using linear regression method and product moment correlation. This study also uses the determinant analysis technique to see the percentage of the contribution of the independent variable (X) in influencing the dependent variable (Y). Hypothesis testing was carried out using the -t test at a significant level of 0.05 for a two-way test at degrees of freedom (dk) = n-2. The independent variable used in this study is Organizational Structure (X) with 7 indicators, namely Division of Work Activities, Organizational Restructuring, evaluation of organizational structure, job placement, education level, work experience and employee skills. The dependent variable in this study is performance with 7 indicators, namely office equipment, work equipment, performance motivation, job description, leadership style, performance evaluation and cooperation. Based on the t-test,.